2014
DOI: 10.2169/internalmedicine.53.2380
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-induced Encephalopathy after Coil Embolization of an Unruptured Internal Carotid Artery Aneurysm

Abstract: A 58-year-old woman developed agraphia and mild right hemiparesis approximately one month after undergoing coil embolization of an unruptured left internal carotid artery aneurysm. MRI performed on day 39 post-coil embolization showed multiple lesions in the white matter with signal hyperintensity on T2-weighted and FLAIR images in the left middle cerebral artery territory. The patient's cerebrospinal fluid exhibited an elevated protein level at 46 mg/dL; however, no other findings suggested another underlying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 14 publications
0
19
0
Order By: Relevance
“…Literature review indicated that symptoms of neurological dysfunction presented within minutes to hours after contrast agent administration, and most patients fully recovered within 48-72 hours. 2,3,5,7,50,51 In our case, the patient presented with hemiparesis, hemianopia, and unconsciousness within minutes of radial sheath removal, and more extreme features developed, such as recurrent seizures, and cardiac and respiratory arrest. Her symptoms resolved completely within 72 hours, which was consistent with the clinical course of CIE. We suspect that the severe symptoms of this patient were related to advanced age, hypertension, and other risk factors, which may have increased BBB permeability.…”
Section: Discussionmentioning
confidence: 68%
“…Literature review indicated that symptoms of neurological dysfunction presented within minutes to hours after contrast agent administration, and most patients fully recovered within 48-72 hours. 2,3,5,7,50,51 In our case, the patient presented with hemiparesis, hemianopia, and unconsciousness within minutes of radial sheath removal, and more extreme features developed, such as recurrent seizures, and cardiac and respiratory arrest. Her symptoms resolved completely within 72 hours, which was consistent with the clinical course of CIE. We suspect that the severe symptoms of this patient were related to advanced age, hypertension, and other risk factors, which may have increased BBB permeability.…”
Section: Discussionmentioning
confidence: 68%
“…The interventional neuroradiology literature reports a limited number of similar or identical cases. However, contrast-induced encephalopathy (Nagamine et al 2014) and granulomatous inflammation due to foreign body emboli consisting of micronized powder particles as used in latex gloves or small cotton fibers from the table gauze (Fealey et al 2008a, b) could also serve as differential diagnosis to this particular condition.…”
Section: Discussionmentioning
confidence: 99%
“…Some scholars think the non-ionic contrast agent will influence blood coagulation and has coagulation effect, while ionic contrast agent has anticoagulation effect. Since relevant reports are few, further study is still required for the mechanism on CIE with cerebral hemorrhage [10].…”
Section: Discussionmentioning
confidence: 99%